Mexico : Detailed Assessment Report-Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2018)
This report provides a summary of the anti-money laundering/combating the financing of terrorism (AML/CFT) measures in place in Mexico. Mexico has a mature AML/CFT regime, with a correspondingly well-developed legal and institutional framework. Most of the key authorities have a good understanding of money laundering (ML) and terrorist financing risks, and there is generally good policy cooperation and coordination. The financial sector demonstrates a good understanding of the primary ML threats from organized crime groups and associated criminal activities as well as tax crimes, but the recognition of corruption as a main threat is uneven. Financial intelligence and other relevant information are made available by the financial intelligence unit and accessed on a regular basis by competent authorities.